Good Governance Aspect in Implementation of The Transparency of Public Information Law - Sakapurnama, Eko; Safitri, Nurul (BISNIS & BIROKRASI: Jurnal Ilmu Administrasi dan Organisasi, 2013)
The Indonesian government has pursued to establish freedom of information for their people in order to enhance good governance in the public sector by implementing the Transparency of Public Information Law Number 14 Year 2008, popularly known as UU KIP. This study is aimed at describing and drawing the factors that affected the implementation of UU KIP in Surakarta City and West Lombok Regency. This research was conducted through a mixed method of a quantitative method through surveys and a qualitative method through in-depth interviews and a focus group discussion. The research concluded that there are numerous factors which affected the implementation of UU KIP such as; political will both from central government and local leader, government ability, flaws in the UU KIP itself, minimum budget, infrastructure, and the culture of the society. UU KIP was also perceived as an Act that regulated the public information and was able to enchance public institutions’ implementation of good governance. The local government is believed to be more accountable and transparant, and able to increase public participation.